Una revisión del movimiento educativo ciencia-tecnología-sociedad - Membiela, Pedro (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
In this paper I present a revision of the Science-Technology-Society movement, its origins, historic development and relations with science education. Comments are made about research carried out on teacher and student opinions about this subject, and the different integration models of STS in the school curriculum. A constructivist curriculum development model is presented and questions related to content selection are considered, as well as teaching models and the conditions that curriculum materials need to fulfill to be considered as STS. Finally, a short revision of the present situation of the STS movement in Spain is made.